Finite-time stability and controller design for a class of hybrid dynamical systems with deviating argument. (February 2021) - Xi, Qiang; Liu, Xinzhi
Abstract: This paper studies the finite-time stability (FTS) for a class of hybrid dynamical systems with deviating argument. An improved hybrid control scheme including sampled-data control as well as impulsive control is presented. Based on the theory of differential equations with piecewise constant argument of generalized type (PCAG) and the method of average impulsive interval (AII), several Lyapunov-based sufficient criteria for FTS are obtained in terms of linear matrix inequalities (LMIs), which can be verified via Matlab. The hybrid controller, in which the sampling instants could be different from the impulse instants, is designed by the established LMIs. The results in present paper are more convenient for application and less conservative than some existing ones. Finally, an example is given to illustrate the effectiveness and advantage of the obtained results.